Pengaruh Advertising, Sales Promotion, Personal Selling dan Publicity terhadap Brand Equity pada PD BPR Bank Sumedang Cabang Tanjungsari - Winda Oktaviana, St Syamsiah; Mintarsih, Mimin (Jurnal Dimamu, 2024)
The background of this study is the lack of intensity of PD BPR Bank Sumedang KC Tanjungsari in promoting advertising, sales promotion, personal selling and publicity, in addition to the amount of competition between banks, both Islamic banks and conventional banks, which affects the decrease in the number of customers. This research aims to determine the influence of advertising, sales promotion, personal selling and publicity on brand equity at PD BPR Bank Sumedang KC Tanjungsari partially and simultaneously. The type of research is associative quantitative with primary data types and uses data collection techniques in the form of observation, interviews, literature studies, questionnaires. Meanwhile, the sampling technique is non-probability sampling with a purposive sampling type. The population is all customers at PD BPR Bank Sumedang KC Tanjungsari in 2023, totaling 5,324 customers with a sample of 99 customers. The data analysis and hypothesis tests used were multiple regression analysis, multiple correlation analysis, determinant coefficient analysis, t-test and F test.  The research results show that advertising, sales promotion, personal selling, and publicity partially influence brand equity by 21.5%, 24.1%, 20.8%, and 29.6%, as well as simultaneously advertising, sales promotion, personal selling and publicity have an effect of 59.6% on brand equity.